Institutional Ownership, Political Connestions and Dividend Payment - Yunita, Ratna; Yulianto, Arief (Universitas Negeri Semarang, 2020)
This study aims to examine the effect of institutional ownership and differences in the average dividend payout policy in the presence of a political connection variable. The population in this study are all companies listed on the Indonesia Stock Exchange in 2008-2017. The sample in this study was based on purposive sampling. The sample of this study were 1157 observations. The analytical method used is a dummy covariance analysis (ANCOVA) regression model. The results showed that institutional ownership had a coefficient value of 0.039768. political connections have a coefficient value of 0.042068. That is, institutional ownership and political connections have a positive influence on dividend payment policies in Indonesia.